Focused ion beam machining of cell culture dish - Ali, Mohammad Yeakub (2008)
Cell culture is one of the major tools in life sciences. In regular cell culture, cells are placed into flat petri dishes made of glass or plastic. As the cells are strongly adhered to the dish, an enzyme treatment is applied to stripe them. In case of nanopillar dish, the cells contact the heads of the pillars then multiply by division supported on top of the nanopillars. The nanopillar structure enabled easy subculture of the cells without conventional trypsinization where the cultured cells can be collected simply by pipetting. However, it remains a challenge to fabricate high aspect ratio metallic or polymeric nanopillars of few hundred nanometer of diameter. This research presents focused ion beam (FIB) maskless sputtering technique for the fabrication of nanopillars sheet to be used in cell culture dish. Nanopore sheet on metallic materials is also machined using FIB which can be used as a master microtool for the mass production of polymer nanopillars sheets by nanoprinting. The typical diameter and height of the nanopillars are 400 nm and 2 ?m respectively.